Assessment of ultrasonic welding process of polycarbonate by employing thermal emission analysis - ŁOZIŃSKI, Janusz (Archives of Acoustics, 1986)
The thermal effects of ultrasonic welding of polycarbonate foil were considered. A contactless method of measuring temperature was developed, applying the emission of infrared radiation from the zone welded ultrasonically. The distributions of the thermal emission in the weld zone were observed on the oscilloscope screen and registered by a 16-mm camera, by recording the stages of the process every 1/32 sec. Measurements were performed of the maximum temperature of the ultra. sonic welding zone of the polycarbonate foil for three vibration amplitudes of the wave-guide instrument: 30, 35 and 40 The wave-guide instrument was under static pressure ranging from 4.21 MPa to 9.64 MPa. The tensile strength of the weld was measured. It was shown that the static pressure and the vibration amplitude influence strongly on the contributions of the internal friction and the friction between the faces of welded polymer to the thermal emission observed.